El Uso del Laboratorio como recurso didáctico en el proceso de la enseñanza-aprendizaje en el área de Ciencias Naturales en el Décimo Año de Educación General Básica de la Unidad Educativa “Simón Rodríguez” periodo 2020 – 2021. - Aguirre Molina, Janeth Patricia. (2021)
This research refers to the use of the laboratory as a didactic resource in the teaching-learning process in the area of Natural Sciences in the Tenth Year of Basic General Education. The problem lay in the non-use of the laboratory due to the lack of training and knowledge of the use of its equipment and materials by the teachers. As a result of this problem, learning was not significant because the laboratory was not used. The objective of the research proposes to elaborate a didactic guide for the use of the laboratory in the teaching-learning process of Natural Sciences of the Tenth Year of Basic General Education. The methodological design was mixed (quantitative and qualitative) non-experimental since the investigative work was directly involved in the virtual school environment, the general methods used are deduction, synthesis, documentary analysis, as a technique the survey of 86 students was developed; survey and interview with 2 teachers. The results obtained suggested the implementation of a laboratory didactic guide to strengthen the teaching-learning process in the area of Natural Sciences to support the teacher in a more playful way. It was concluded that the didactic guide for the use of the laboratory gave an answer to a palpable problem in the Educational Unit, due to the motivation that the students found when carrying out the experimental practices with the interest and enthusiasm for learning the subject of Natural Sciences in the laboratory leading students to be critical and reflective